The Re-integration of College Innovation and Entrepreneurship Education Under Young Entrepreneurs’ Enterprising Spirit and Professional Music Education - Qu, Xiaoyu; Cheng, Lei; Cheng, Ding; Zhang, Shanshan (Frontiers in Psychology, 2022)
The purpose is to coordinate the relationship between innovation and entrepreneurship education (IEE) and professional education. This exploration is based on the entrepreneurial spirit of young entrepreneurs and the re-integration of IEE and music education in colleges. First, the IEE is studied in theory. Then, the basic criteria for integrating IEE and professional education are studied, and 305 students from a music college in Xi'an are taken as the survey sample. The questionnaire is adopted to investigate the current situation of the integration of IEE and professional education. The results show that 52.1% of students believe that IEE is closely related to professional education. In terms of self entrepreneurship awareness, males' awareness of self entrepreneurship is higher than females', and the willingness of self entrepreneurship from freshman to senior is 3.1%, 15.5%, 26.1% and 30.8%, respectively. For the dominant position in the integrated curriculum, 55.6% hold that professional courses should dominate innovative professional courses, and 25.9% believe that innovation and entrepreneurship courses should be dominated. Besides, 16.5% think that the proportion of the two should be the same, and 2% hold that it doesn't matter. For the enthusiasm of innovative professional courses, only 14.1% of students are very positive. The survey results show that the integration of IEE and professional education needs to be improved, and there is a lack of pertinence and guidance for students of different genders and grades. Students are not clear about the position of IEE and lack enthusiasm. Finally, reasonable suggestions are put forward in view of the above problems. The results are conducive to promoting and accelerating the process of talent training mode combining professional education and IEE. It has a certain reference value for college education and teaching reform.